Peran Reputasi Pajak dalam Memediasi Pengaruh Literasi Keuangan dan Orientasi Kewirausahaan terhadap Kepatuhan Pajak Pelaku UMKM di Yogyakarta - Reza Widhar Pahlevi; Siti Resmi; Bintang Lazuardi Benteng Buana Muslim (Jurnal Perilaku dan Strategi Bisnis, 2026)
This study aims to analyze the influence of financial literacy and entrepreneurial orientation on MSME tax compliance, with tax reputation as a mediating variable. Tax compliance is a crucial factor in supporting MSMEs' contribution to state revenue, therefore, understanding the factors that influence it is essential. This study employed a quantitative approach with a non-probability sampling technique using a purposive sampling method. The sample consisted of 216 Micro, Small, and Medium Enterprises (MSMEs) in the Special Region of Yogyakarta. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that financial literacy had no significant effect on MSME tax compliance. Conversely, entrepreneurial orientation was shown to have a positive and significant effect on tax compliance. Furthermore, financial literacy had a positive and significant effect on tax reputation, indicating that good financial understanding can enhance taxpayer image and credibility. Entrepreneurial orientation also had a positive and significant effect on tax reputation. Furthermore, tax reputation was shown to have a positive and significant effect on tax compliance. These findings indicate that tax reputation plays a crucial role in encouraging MSME tax compliance. This research provides implications that efforts to increase tax compliance are not only through strengthening financial literacy, but also through developing entrepreneurial orientation and establishing a positive tax reputation among MSME actors.